Discourse Markers in Science Articles in Linguistics (Proceedings of Southern Federal University. Philology, 2017)
Olga G. Melnik, Aellina A. Sidelnik (Rostov-on-Don, Russian Federation)This article presents a comparative analysis of the functioning of discourse markers in the written scientific discourse. The material of the study is based on the English-language and Russian-language articles on linguistics. Semantic classification was used for the systematization of the material studied. An attempt was made to identify the ethno-linguistic features of the use of discourse markers.Key words: scientific discourse, discourse markers, classification of discourse markers, comparative analysis.